The Influence of Employee Emotional Behavior and System Factors on the Organizational Efficiency of Trouser Automatic Hanging System - Huo, Yarui; Faridah, Sahari (Wolters Kluwer Health, Inc., 2023)
Background: The trouser production industry is in the transformation and upgrading of the attack period. Intelligent manufacturing is an important strategic direction for the transformation and upgrading of China's manufacturing industry, the emotional behavior of employees affects the organizational efficiency of the trouser production line, and the study of organizational efficiency is the core of automated production in the face of the new pattern of industry development, the trouser production line managers fully consider the emotional behavior of employees, the introduction of automated equipment to help improve the organizational efficiency of the production line It is imperative to do so. Subjects and Methods: This paper explores the factors influencing the introduction of an automated hanging system in trouser production lines in four dimensions: employee emotional behavior, i.e., intention to use, user satisfaction, and system quality and organizational efficiency, and constructs a theoretical model of organizational efficiency of an automated transfer hanging system. This study was conducted with 268 front-line employees in a Chinese trouser manufacturing company and analyzed by structural equation modeling (SEM). Results: The results showed that (i) system quality had a significant positive effect on employees' emotional behavior, i.e., intention to use and user satisfaction; (ii) user satisfaction had a significant positive effect on intention to use. (iii) Employee's emotional behavior, i.e., intention to use and user satisfaction, positively affects organizational efficiency. Conclusions: This study addresses the results of the study, fully considers the direct and positive impact of employees' emotional behavior on the organizational efficiency of the automatic hanging system, and puts forward practical and feasible guiding suggestions for trouser manufacturing enterprises to introduce automated equipment and enhance their automation and intelligent development capabilities based on meeting employees' emotional needs. Keywords: Emotional behavior, intelligent manufacturing, hanging production line, production efficiency, system quality, structural equation modeling